Respiratory bellows‐gated late gadolinium enhancement of the left atrium. Issue 5 (29th November 2012) - Peters, Dana C.; Shaw, Jaime L.; Knowles, Benjamin R.; Moghari, Mehdi Hedjazi; Manning, Warren J.
Abstract : Purpose: To compare bellows‐gated late gadolinium enhancement (LGE) with standard navigator‐gated (NAV‐gated) LGE for left atrial (LA) imaging, to eliminate the inflow artifacts associated with NAV‐gating. Materials and Methods: Eleven subjects, including six patients with atrial fibrillation (AF), were imaged with a 3D free‐breathing NAV‐gated and bellows‐gated LGE. Motion compensation was compared by blinded grading of image sharpness and motion ghosting (0 = worst, 2 = best). Inflow artifacts in the right inferior pulmonary vein (RIPV) and right superior PV (RSPV) were characterized on the same scale (0 = none, 2 = prominent). In patients, each PV was divided into four quadrants circumferentially in order to assess agreement about scar presence on both image sets. Results: Respiratory compensation was not different (1.7 ± 0.5 vs. 1.6 ± 0.5, sharpness, 1.6 ± 0.5 vs. 1.6 ± 0.5, ghosting, P = NS) for bellows‐ and NAV‐gated images. For NAV‐gated LGE, inflow artifacts were more prominent in the RSPV than the RIPV (1.2 ± 0.8 vs. 0.7 ± 0.5, P = 0.046). Visually, inflow artifacts both obscured and mimicked the true scar. Disagreement on the presence of scar was found in 18% of the assessed quadrants, with 25% disagreement for RSPV quadrants ( P = 0.01). Conclusion: Bellows‐gated LGE provides similar respiratory compensation as NAV‐gating, without inflow artifacts, leading to improved assessment of scar presence. J. Magn. Reson. Imaging 2013;38:1210–1214. © 2013 Wiley Periodicals, Inc.